1999
DOI: 10.1212/wnl.53.7.1584
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcome in pneumococcal meningitis correlates with CSF lipoteichoic acid concentrations

Abstract: Lipoteichoic and teichoic acids are components of the cell wall of Streptococcus pneumoniae. A recently developed enzyme immunoassay was used in patients with pneumococcal meningitis to investigate lipoteichoic and teichoic acid concentrations in CSF at the first lumbar puncture in relation to the clinical outcome determined by the Glasgow Outcome Scale. Lipoteichoic and teichoic acid concentrations in CSF were significantly associated with neurologic sequelae and mortality in S. pneumoniae meningitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(58 citation statements)
references
References 11 publications
1
56
0
1
Order By: Relevance
“…Several studies have shown that LTA can be released from actively growing streptococci in vitro (48 -51), and it has also been shown that individuals infected with streptococci can have LTA levels that exceed the concentrations we have used in this study, in cerebrospinal fluid, for example (52). Because S. pyogenes produces two potent hemolysins, streptolysin S and streptolysin O, local concentrations of Hb during a typical course of infection could be even higher than normal levels of free Hb in plasma.…”
Section: Discussionmentioning
confidence: 76%
“…Several studies have shown that LTA can be released from actively growing streptococci in vitro (48 -51), and it has also been shown that individuals infected with streptococci can have LTA levels that exceed the concentrations we have used in this study, in cerebrospinal fluid, for example (52). Because S. pyogenes produces two potent hemolysins, streptolysin S and streptolysin O, local concentrations of Hb during a typical course of infection could be even higher than normal levels of free Hb in plasma.…”
Section: Discussionmentioning
confidence: 76%
“…The clinical relevance of this finding is underlined by the fact that pneumococcal cell wall components, a known TLR2 agonist (30,31), are excessively released after antibiotic-induced lysis of bacteria and that patient outcome is correlated to their concentration in the CSF (32). The ubiquitous presence of lipopeptides on bacterial surfaces, including other meningitis-inducing pathogens, further broadens the clinical importance.…”
Section: Discussionmentioning
confidence: 99%
“…During disease, BBB cells are exposed to pneumococci and PCW, with PCW persisting at the site of infection well beyond the period of bacterial viability (29). To assess direct cytotoxic effects of pneumococci and PCW, we exposed primary BMECs to living bacteria (D39; 10 6 , 10 7 and 10 8 CFU/ml) or PCW (equivalent of 10 6 , 10 7 , 10 8 and 10 9 CFU/ml) at concentrations relevant for human bacterial meningitis.…”
Section: Pneumococci and Pcw Induce Apoptosis In Bmecsmentioning
confidence: 99%
“…These components keep inflammation going, fuel tissue destruction in later stages of disease, and impede repair. In particular, the concentration of PCW in the CSF is directly correlated to a poor outcome of meningitis (29). TLR2, a critical receptor in innate immune response, is directly involved in cell wall-associated endothelial cell death.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation